The ancient Near East history, society and economy - Liverani, Mario 1939- (Routledge, 2014)
The ancient Near East as a historical problem -- The geography of the ancient Near East -- The Neolithic and Chalcolithic periods -- The urban revolution -- The rise and fall of the first urbanisation -- Mesopotamia in the early dynastic period -- The rise of Ebla -- The Akkadian empire -- The third dynasty of Ur -- The crisis of the second urbanisation -- The "intermediate period" of Isin and Larsa -- The old Assyrian period -- The Mari age -- Hammurabi of Babylon -- Anatolia in the old Hittite period -- The late Bronze Age : technologies and ideologies -- The rise of Mitanni -- The Hittite empire -- Syria and the Levant in the late Bronze Age -- The middle Assyrian kingdom -- Kassite Babylonia -- Crisis and reorganization -- Israel -- The Phoenicians -- The Arameans in Syria and Mesopotamia -- The neo-Hittite states -- Assyria, Babylonia, and Elam in the 12th to 9th century BC -- The rise of the neo-Assyrian empire -- The structure of the neo-Assyrian empire -- The periphery of the neo-Assyrian empire -- The fall of the empire and the rise of the Chaldeans -- The Medes and the rise of the Persians
"Originally published in Italian as Antico Oriente ; 1988, 2011, Gius. Laterza & Figli.". - Includes bibliographical references and index
Keywords: Geschichte; Wirtschaft; Gesellschaft; Naher Osten; Middle East / History / To 622; Alter Orient